Identifikacija verig vrednosti v slovenskem gozdno-lesnem biogospodarstvu - Straže, Aleš (Les (Ljubljana), 2023)
The Slovenian forestry and timber industry are primarily about creating value and delivering the desired products to customers or users, multiplying the impact throughout the forest-wood value chain through the functioning of all its links. It is important to understand the performance of the entire value chain from the point of view of the potential of the achievable volumes, the level of technological processing and the marginal quality of the input raw materials and the characteristics of the manufactured products. The aim of this study was to map the individual value chains in the entire domestic forest-wood value chain, to analyse the functioning of the circular economy and the potential for processing hardwood into high-tech materials and high value-added products. We identified five primary value chains (P1...P5), two chains to ensure a circular economy (K6, K7), and three chains of higher processing stages to produce higher value-added products (S8...S10). In hardwood processing, the non-functioning of the primary chain "Veneer" (P2) and the limited functioning of the chain "Lumber" (P1) are of concern, which means that we are not using the potential of the highest value wood raw material. In order to achieve the so-called criterion of green value chains, it is necessary to strengthen the chains that ensure a circular economy (K6 – Residues, K7 – Waste wood), which currently function at a lower level and are phasing out too quickly.
Keywords: bioeconomy; biogospodarstvo; forest-wood chain; gozdno-lesna veriga; value chains; verige vrednosti